EFEKTIVITAS ISI PIRINGKU SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN GIZI PADA ANAK - Ayuningtiyas, Aisyah Nilam; Ni'mah, Dzurrotun Putri; Setiyowati, Mellya Ayu; Ni'mah, Nazilatun; Caesar, David Laksamana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2023)
Stunting in Indonesia is a serious threat that requires appropriate handling. Based on data from the Indonesian Toddler Nutrition Status Survey (SSGBI) in 2022, the prevalence of stunting in Indonesia reached 21,6%. This means that around one in four children under five (more than eight million children) in Indonesia is stunted. The figure is still higher than the threshold set by WHO, namely 20%. (SSGI, 2022). The type of research used is quantitative. This research design is pre-experimental with a one-group pretest and posttest design. The total sample used in this research was 65 respondents. The research results showed a significant difference in the average student knowledge scores before and after intervention using the ISI PIRINGKU method with a p-value of 0.0001. This means that the ISI PIRINGKU method is effective in increasing students' knowledge about nutrition